Precast and Prestressed Concrete for the Future Construction of Sudurpaschim - Gautam, Bishnu Prasad (Far Western Review, 2023)
Concrete is the second most consumed material in the earth after water. While concrete has been used for more than 2000 years, widespread use of precast elements has emerged as the latest concrete technology for quality of construction. Precast concrete follows modular construction approach which is sometimes classified as one of the top ten construction innovations. The widespread application of precast concrete was augmented by the invention of prestressed concrete as a revolutionary technology in concrete. This study provides an overview of the use of precast and prestressed concrete technology in Nepal. It highlights the benefits of concrete for national economy by utilizing domestic resources and in realizing sustainable development through durable construction. Recent applications of precast and prestressed concrete in Nepal are highlighted, with examples from various structures including building, river training, and slope stability, hydropower and tunnel projects. The challenging aspects of precast and prestressed construction are also illustrated with examples. Research and development of precast and prestressed concrete products in Nepal are highlighted by presenting the initiatives from experimental studies and academic research. Even though Nepal is in the early stage of application of precast and prestressed concrete technology, the initial applications indicate huge potential and great benefits of application of such products for the faster, cost-effective and durable construction in various parts of Nepal.